Analysis of secondary metabolites present in the plants Cynara scolymus L and Artemisia absinthium L during the treatment of dyslipidemia - Menezes, Dâmares Cardoso; Santos, Tayanne Andrade dos; Portela, Fernanda Santos (O Mundo da Saúde, 2024)
The use of medicinal plants as a form of treatment for various diseases is a tradition that has spanned generations for thousands of years. Ancient people used to use specific parts of some vegetables to make teas and dressings for wounds. Even today, many people prefer natural forms as a treatment for their comorbidities, especially as adjuvants in the fight against dyslipidemia. The present work aimed to analyze the plants Cynara scolymus L and Artemisia absinthium L to confirm the presence or absence of specific proteases against hypercholesterolemia. The research was carried out by screening the plants using the RCSB software (https://www.rcsb.org/). In the end, it can be confirmed that the Cynara scolymus L plant meets the prospects for treating hypercholesterolemia, while Artemisia absinthium L did not present sufficient values that are effective in the treatment.